OPTIMIZATION OF PHARMACOTHERAPY OF PATIENTS WITH CHRONIC HEART FAILURE FUNCTIONAL CLASS II ON INFLUENCE ON THE REGULATORY AND ADAPTIVE STATUS - S. V. Rutenko (Кубанский научный медицинский вестник, 2014)
The study involved 100 people (50 men and 50 women) aged 32 to 68 years. The first group consisted of 53 patients with chronic heart failure class II and III stage of hypertensive disease (29 men and 24 women, age 52,9±10,7 y. o.), treated with sustained-release metoprolol succinate (betaloc ZOK of «AstraZeneca», Sweden production, of 97,3±9,5 mg/day doze). The second group included 47 patients with chronic heart failure class II and III stage of hypertensive disease (21 men and 26 women, age 57,5±5,7 y. o.), receiving quinapril (accupro of «Pfizer», USA production in 24,7±13,4 mg daily doze. Treadmill activity with measuring of the maximum oxygen consumption on effort, 24-hour blood pressure monitoring, echocardiography and NT-proBNP testing, сardio-respiratory synchronism trial was carried out initially and after six months of therapy. Beta-blocker and angiotensine converting enzyme inhibitor are equally reducing blood pressure, are not identical in influencing the in statedly-adaptive status patients and the latter can be preferred.